Implementing collaborative pre-task planning with intermediate Arab EFL learners in a blended, task-based environment: A mixed methods study - Osama Alzoubi (Ampersand)
Pre-task planning (PTP) has received scant attention in L2 writing and task-based research, especially pertaining to its effect on the writing production of intermediate, school L2 learners. This study examines mainly the influence of implementing collaborative PTP on the writing production of Arab EFL learners within blended, task-based environment. Following a mixed methods experimental design, intermediate L2 learners were distributed in planning and no-planning conditions and conducted a pre- and post-test. Students in both groups composed a number of argumentative essays over a 10-week period, which were analyzed for complexity, accuracy, fluency, ideational content, and lexical richness. Results from independent samples t-test and univariant analysis of covariance (ANCOVA) indicated several significant differences between participants' performance on the post-test compared to the pre-test but with differential effects in terms of the five measures. Analyses revealed that PTP didn't promote all the measures simultaneously, but it mainly assisted L2 writers produce enhanced content planning (idea generation, lexis, and argumentation) and resulted in greater fluency and overall improved organization and writing quality. Results of classroom observations supported the statistical results and showed that blended, task-based PTP positively impacted students' writing performance, motivation, self-confidence, and learning independence, and thus created a positive, engaging L2 writing environment. The study results were interpreted through the lens of cognitive processing theories, particularly Skehan's (1998, 2014) Limited Attentional Capacity Model and Robinson's (2001) Cognition Hypothesis, providing support to Robinson's position that PTP led to greater fluency. The use of data and methodological triangulation in this study offers new insights into the role of PTP in the L2 writing process, especially with intermediate, school learners in an authentic classroom setting, and thus contributes to the inconsistent results of previous PTP studies (Ellis, 2021).